SIFAT CAMPURAN ASPAL KERAS YANG MENGANDUNG BITUMEN ASBUTON UNTUK KONSTRUKSI CAMPURAN BERASPAL - Furqon Affandi (Jurnal Jalan-Jembatan, 2007)
Asphalt has a great influence on asphalt mixes, therefore determination of asphalt grade needs to be adopted to temperature where asphalat used. The asphalt type that commonly used in Indonesia is asphalt cement pen 60 besides some other types such as polymer asphalt or modified asphalt. The article describes asphalt cement pen 60 modified with pure asbuton bitumen (mineral content less than one percent), considering that asbuton as agreat Indonesia natural deposit. Research analysis shows that the addition of asbuton bitumen resulting in more harden asphalt and resistant to high temperature proved by the increase of softening point value, and more low susceptibility. Dynamic Shear Rheometer (DSR) test was conducted with various asbuton bitumen contents. The range of suited asphalt temperatures was obtained for each asphalt mix containing asbuton bitumen, related to resistance of permanent deformation and fatigue cracks. Asphalt containing asbuton bitumen is more resistance of deformation and crack to higher temperature compare to cement asphalt without asbuton bitumen, so that asphalt containing asbuton bitument is suitable for tropical climate like Indonesia. Keywords : Asbuton Bitumen, penetration, so ftening point, Dynamic Shear Rheometer, deformation, cracks .